Average Glandular Dose (AGD) and breast density mammogram guidelines / Nurul Dizyana Nor Azman - Nor Azman, Nurul Dizyana (2020)
Introduction/background: The aim of mammography examination is to detect, determine and evaluate breast cancer and other breast pathologies. Mammography had been proven to be most effective method to detect breast carcinoma. GE Senographe FFDM system operates with three automatic optimization parameters (AOP), namely: contrast (CNT), standard (STD) and dose (DOSE). Higher breast density has been strongly associated with increase breast cancer. Thus, measurements of breast density are important for risk assessment and prevention strategies, Knowledge of the ranges of breast density in patient is important when planning for breast screening. Objective: to develop a reference table for mammographers according to breast density of patient. Method: A mammographic breast phantom (012A) set were used for this research are 40 mm thickness with 30%, 50% and 70% breast density composition were exposed using Mammography machine GE Senographe FFDM. The exposure was performed using three settings, exposure was selected by default with setting, AOP; (STD, CNT and DOSE) were switched ON. AGD and mAs were recorded. Result: 70% breast density type recorded highest AGD compare with other breast type and DOSE setting produce lowest mAs among others. Conclusion: A reference table was developed for mammographers in determine which setting is suitable for patient.